2002
DOI: 10.1002/ccd.10198
|View full text |Cite
|
Sign up to set email alerts
|

Screening for subclavian artery stenosis in patients who are candidates for coronary bypass surgery

Abstract: We prospectively evaluated 59 patients who were deemed candidates for coronary bypass surgery after coronary artery angiography for subclavian artery narrowing, which could compromise the ipsilateral internal thoracic artery graft. Bilateral arm blood pressure (BP) measurements, auscultation for supraclavicular or cervical bruits, and questioning about cerebrovascular ischemic symptoms were compared to brachiocephalic-subclavian arteriography. One neurologic complication occurred during arteriography. An upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 8 publications
3
49
1
7
Order By: Relevance
“…However, the variability resulting from these interactions is considered trivial compared with the greater ABI variability between different subjects. The variability of ankle pressures was found to be similar to that of arm pressures in 3 reports, 2,181,189 whereas in 5 other studies, 157,166,167,196,201 a better reproducibility of the arm pressures was reported. Overall, data demonstrate that the ABI is a valid biological parameter.…”
Section: Overall Reliability and Reproducibility Of Abi Measurementsupporting
confidence: 52%
See 1 more Smart Citation
“…However, the variability resulting from these interactions is considered trivial compared with the greater ABI variability between different subjects. The variability of ankle pressures was found to be similar to that of arm pressures in 3 reports, 2,181,189 whereas in 5 other studies, 157,166,167,196,201 a better reproducibility of the arm pressures was reported. Overall, data demonstrate that the ABI is a valid biological parameter.…”
Section: Overall Reliability and Reproducibility Of Abi Measurementsupporting
confidence: 52%
“…Differences in SBP between arms may occur in the case of subclavian artery stenosis. Osborn et al 201 reported 100% sensitivity and specificity to detect Ͼ50% subclavian stenosis when the interarm blood pressure difference exceeded 15 mm Hg. Thus, subclavian artery stenosis should be suspected when the SBP difference between both arms is Ն15 mm Hg.…”
Section: Standard Calculation Of the Abimentioning
confidence: 99%
“…Similar studies with much fewer subjects but using a systolic cut-off of 15 and 20 mmHg found positive predictive values of 100% and 67%, respectively, both with 100% negative predictive values. 10,11 As such, a systolic cuff pressure difference or gradient (in the case of invasive assessment) of > 10 mmHg can be used to delineate hemodynamic significance and justify further investigation.…”
Section: Physical Examinationmentioning
confidence: 99%
“…The prevalence of significant left subclavian artery stenosis in patients referred for CABG is reported to be 0.2% to 6.8% (1,(11)(12)(13)(14). The prevalence in ESRD patients appears to be higher because peripheral artery diseases coexist more frequently.…”
Section: Discussionmentioning
confidence: 99%